Phenomenology Analysis of Functional Bureaucratic in Budget Abuse - Azhar, Insyira Yusdiawan; Ishomuddin; Sukmana, Oman; Febriansyah, Ferry Irawan (International Journal of Law and Society, 2023)
This research aims to look micro-based on the subject's experience of how several bureaucratic actors in small towns commit the phenomenon of budget abuse. The research method used is a qualitative approach with a phenomenological research type. The primary data was obtained by interviewing five main informants and field observations, while the secondary data was obtained from various related encyclopedia sources. Data analysis used Moustakas' theory by reading interview transcripts, horizonalization, a cluster of meaning, and developing textural descriptions to validate reflexity, credibility, and transferability. This study's results reveal how corruptors' actions are more motivated by a person's scientific attitude, which is based on social a priori as explained by classical phenomenology, compared to situational factors that are felt by the body as initiated by neo-phenomenology.